2021
DOI: 10.3390/ani11092510
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography in the Study of Animals’ Emotional Responses: A Critical Review

Abstract: Whether animals have emotions was historically a long-lasting question but, today, nobody disputes that they do. However, how to assess them and how to guarantee animals their welfare have become important research topics in the last 20 years. Infrared thermography (IRT) is a method to record the electromagnetic radiation emitted by bodies. It can indirectly assess sympathetic and parasympathetic activity via the modification of temperature of different body areas, caused by different phenomena such as stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 98 publications
1
53
0
Order By: Relevance
“…Therefore, in the case of horses used for riding, other more specific indicators of equine well-being are required to assess rider:horse interaction. Recently, the infrared thermography (IRT) measurement of the selected regions of the body surface temperature was proposed to assess both the horse’s emotional state [ 18 , 19 , 20 ] and the horse’s physiological response to an effort [ 17 , 21 , 22 , 23 ], also including the evaluation of the impact of the rider:horse bodyweight ratio on the equine organism [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the case of horses used for riding, other more specific indicators of equine well-being are required to assess rider:horse interaction. Recently, the infrared thermography (IRT) measurement of the selected regions of the body surface temperature was proposed to assess both the horse’s emotional state [ 18 , 19 , 20 ] and the horse’s physiological response to an effort [ 17 , 21 , 22 , 23 ], also including the evaluation of the impact of the rider:horse bodyweight ratio on the equine organism [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for the noninvasive nature of temperature assessment, it should be further applied to research on animals in AAIs. A recent review provides further data on the benefits and challenges of infrared thermography in assessing animal emotional states [102].…”
Section: New Research Methodsmentioning
confidence: 99%
“…It has been established that those behavioral problems in dogs are probably associated with a close relationship to humans. Hence it is vital to avoid these states [ 112 ], as Mariti et al demonstrated [ 107 ]. Those researchers further concluded that the dog owners did not require experience to identify these negative emotions accurately.…”
Section: Emotions In the Dogmentioning
confidence: 99%
“…As can be seen, comprehending the emotions and affects of heterospecifics is of great significance for domestic species, such as dogs [ 110 ]. Recognition of emotions, mimicry, and gestures is considered of greater importance than other forms of expression [ 115 ], though facial mimicry does not necessarily accurately reflect the meaning of the underlying emotion [ 112 ]. This phenomenon has also been identified in dogs because their ability to recognize certain expressions shown by individuals in their social circle—whether of the same or a different species, including humans—allows them to generate similar or opposing responses to those manifestations.…”
Section: Emotions In the Dogmentioning
confidence: 99%